Europe, where to? - Valeriu Ioan-Franc; Napoleon Pop; Andrei Marius Diamescu (Amfiteatru Economic, 2023)
The authors review the challenges that the Romanian economy and society had to face in the European and global geoeconomic context. Starting from the perspectives advanced by the international economic fora, the risks the European economy will have to answer through counteracting and general resuscitation measures and means are analysed with the rigour due to academic research. In this context, a series of aspects of major interest for Romania are comprised, which we both under the pressure of its objectives registered in PNRR as well as the ones developed as risks in the proximity of the Russian-Ukrainian war, as part of NATO and the EU.
Keywords: E3; E4; E5; E6; F1; F3; F4; F5; G1; O10; 330; economic growth; economic crisis; energy crisis; public debt; taxation; geopolitics; geoeconomics; inflation; monetary policy.